The effect of soil Texture and apparent density on the growth and development of root systems of maize - Abdul-Khadum, Suad (Al-Adab Journal, 2020)
The growing of plants in loam-sandy soils and loam soils is higher than in other soil types such as mud soils due to the very little space between the grains for air and water to circulate. The dry weight of roots and length of maize are higher in loam-mud soils and sandy soils than in mud soils. The decrease in length of maize results in the ability of maize to absorb water and nutrition. The research paper has come up with; The highest value of maize length has been recorded in soils with density of (28-60) because the space between the particles is relatively good.The lowest value of maize length has been recorded in soils with density of (80) because such soils are badly ventilated.The highest average value for maize leaves has been recorded in soils with density of (40).The lowest value of growing maize has been recorded in soils with density of (80) because the conditions of ventilation, absorptivity and space are bad.The highest value of vegetative growth has been recorded in soils with density of (0-17).